The effect of non-dental e-glass fiber position on the hardness of glass fiber reinforced composite in fixed dentures: Study experimental - Al Isra, Muhammad Firman; Sari, Widya Puspita; Darmawangsa, Darmawangsa (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRAKPendahuluan Gigi tiruan menjadi solusi yang tepat untuk menggantikan gigi yang hilang. Gigi tiruan jembatan dengan bahan porcelain fused to metal paling sering digunakan dalam praktik klinis, namun memiliki kekurangan seperti efek alergenik dan efek toksisitas yang dapat disebabkan oleh bahan logam, rentan pecah, memerlukan beberapa kali kunjungan, dan membutuhkan preparasi gigi abutment yang cukup luas. Alternatif bahan yang dapat digunakan untuk gigi tiruan cekat adalah Fiber reinforced composite dengan E-glass fiber dental yang memiliki kelebihan seperti biokompatibilitas baik, memiliki kekuatan kompresi dan estetika yang baik. Ketersediaan E-glass fiber dental di Indonesia masih terbatas dengan harga yang cukup mahal. E-glass fiber non dental secara umum telah digunakan di bidang teknik. E-glass fiber non dental memiliki komposisi yang sedikit berbeda dengan E-glass fiber dental. Tujuan dari penelitian ini untuk mengetahui pengaruh posisi E-glass fiber non dental terhadap kekerasan Fiber reinforced composite. Metode: Penelitian eksperimental dengan Fiber reinforced composite dengan E-glass fiber non dental dengan 3 kelompok sampel yang teridiri dari kelompok posisi tension side, kelompok compression side, dan kelompok neutral axis yang masing masing terdiri dari 6 sampel. Sampel diuji dengan vickers hardness tester dengan beban 100gf selama 15detik, jejak indentasi dihitung untuk mendapatkan vickers hardness number (VHN). Hasil: Hasil uji pada Fiber reinforced composite dengan fiber pada posisi tension side memiliki kekerasan tertinggi dengan nilai 45,77 VHN. Fiber reinforced composite dengan fiber pada neutral axis 43,35 VHN. Fiber reinforced composite dengan fiber pada compression side memiliki nilai terendah 39,60 VHN. Simpulan: Kesimpulan dari penelitian ini bahwa terdapat pengaruh posisi E-Glass fiber non dental terhadap kekerasan Fiber reinforced composite.KATA KUNCI: E-glass fiber, Fiber reinforced composite, posisi fiber, kekerasanThe Effect of Non-dental E-glass Fiber Position on the Hardness of Glass Fiber Reinforced Composite in Fixed DenturesABSTRACT Introduction: Dentures are the right solution to replace missing teeth. Denture bridges made from porcelain fused to metal are the most frequently used in clinical practice, but they have disadvantages such as allergenic and toxicity effects that can be caused by metal materials, are prone to breaking, require several visits, and require extensive preparation of the abutment teeth. Alternative materials that can be used for fixed dentures are fiber-reinforced composites with E-glass dental fiber, which have advantages such as good biocompatibility, compression strength, and aesthetics. The availability of E-glass fiber dental in Indonesia is still limited, with prices being quite expensive. Non-dental E-glass fiber has generally been used in the engineering field. Non-dental E-glass fiber has a slightly different composition from dental E-glass fiber. The aim of this research is to determine the effect of the position of non-dental E-glass fiber on the hardness of fiber-reinforced composites. Method: Experimental research with fiber-reinforced composite with non-dental E-glass fiber with 3 sample groups consisting of the tension side position group, compression side group, and neutral axis group, each consisting of 6 samples. The sample was tested with a Vickers hardness tester with a load of 100 gf for 15 seconds, and the indentation trace was calculated to obtain the Vickers hardness number (VHN). Results: The test results on fiber-reinforced composites with fiber in the tension-side position had the highest hardness with a value of 45.77 VHN. Fiber composite reinforced with fiber on the neutral axis is 43.35 VHN. Fiber-reinforced composites with fiber on the compression side have the lowest value of 39.60 VHN. Conclusion: The conclusion from this research is that there is an influence of the position of non-dental E-Glass fiber on the hardness of fiber-reinforced composites.KEY WORDS: E-glass fiber, Fiber reinforced composite, fiber position, hardness